The resiliency of the UN staff member’s oath of office - Andrea Angeli (Freedom from Fear, 2020)
This is not the first time that I have been asked how we can succeed in advancing the values of the United Nations in the most critical situations. It is a good question. Even those who have served in peace missions for over thirty years cannot provide a single answer to this question.